Designing pedagogic strategies for dialogic learning in higher education. Issue 2 (14th March 2016) - Simpson, Alyson
Abstract : This article focuses on the pedagogic value of dialogue to strengthen pre-service teachers' reflective practices and improve their knowledge about the power of talk for learning. Dialogic learning was introduced to a unit of study taken by a final-year cohort of students in an initial teacher education degree at an urban university in Australia. Various opportunities for dialogue were designed into the unit through blended learning such as face-to-face tutorials, social networks and Viva Voce contexts. In the face of mixed opinion on their efficacy, the author profiles the use of social networks as a means of incorporating more interactive discourse through Web 2.0 platforms in higher education. The mixed-methods study reports on data collected from focus group interviews run at the end of the semester. An analytical framework based on Alexander's principles of dialogic learning is used to interrogate the data set. The results illustrate the positive impact that dialogue employed as a pedagogic tool had on the value students perceived of their learning experience. It is recommended that designs for learning in higher education incorporate iterative exchanges across a variety of blended learning contexts to encourage productive interactions between students, peers and tutors.